2020
DOI: 10.3390/ijms21051692
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning Induces Cardioprotective Autophagy and Signals through the IL-6-Dependent JAK-STAT Pathway

Abstract: Autophagy is a cellular process by which mammalian cells degrade and assist in recycling damaged organelles and proteins. This study aimed to ascertain the role of autophagy in remote ischemic preconditioning (RIPC)-induced cardioprotection. Sprague Dawley rats were subjected to RIPC at the hindlimb followed by a 30-min transient blockade of the left coronary artery to simulate ischemia reperfusion (I/R) injury. Hindlimb muscle and the heart were excised 24 h post reperfusion. RIPC prior to I/R upregulated aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 137 publications
(158 reference statements)
1
19
1
Order By: Relevance
“…4 and 7 ). These findings are consistent with our previous reports showing that RIC increases autophagy signaling in several different models [ 25 , 26 , 47 49 ]. However, in some reports, albeit in different models with different RIC protocols (in large animals subjected to intracoronary doxorubicin infusion [ 31 ], an acute human cardiac surgical intraoperative study [ 32 ] and doxorubicin toxicity in a mouse model [ 33 ]) have shown that RIC has no effect or even decreases autophagy signaling, emphasizing the need for disease-specific models in regard to the effects of RIC.…”
Section: Discussionsupporting
confidence: 94%
“…4 and 7 ). These findings are consistent with our previous reports showing that RIC increases autophagy signaling in several different models [ 25 , 26 , 47 49 ]. However, in some reports, albeit in different models with different RIC protocols (in large animals subjected to intracoronary doxorubicin infusion [ 31 ], an acute human cardiac surgical intraoperative study [ 32 ] and doxorubicin toxicity in a mouse model [ 33 ]) have shown that RIC has no effect or even decreases autophagy signaling, emphasizing the need for disease-specific models in regard to the effects of RIC.…”
Section: Discussionsupporting
confidence: 94%
“…The isolated hearts were mounted on the Langendorff system and perfused with perfused with Kreb's Henseleit solution at 37°C. The inflow of physiological solution was stopped for 30 minutes to induce global ischemia and afterwards, the flow of KH was reinstituted for 120 minutes to establish reperfusion 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that resident splenic (and possibly circulating) T cells and B cells were the sources of the SnPP-triggered the five-to sevenfold plasma IL-10 increases. Although IL-6 has long been considered to be a pro-inflammatory cytokine, it also exerts potent anti-inflammatory effects (Billah et al, 2019(Billah et al, , 2020Filho et al, 2015;Kimizuka et al, 2004;McGinnis et al, 2015;Nechemia-Arbely et al, 2008). As examples, IL-6 can suppress production of pro-inflammatory cytokines and their receptors.…”
Section: Discussionmentioning
confidence: 99%